Aciertos y defectos de la protección jurídica de los conocimientos tradicionales en el Perú - Sierra Roque, Nicole Alexandra (2022)
Peru is a diverse country, and traditional knowledge (TK) is found within this diversity. TK is an intellectual product and is part of the identity (culture and values) and the sustainable development of indigenous communities. Based on them, it is possible to generate advances in different sciences, such as medicine and other technologies. However, there is a latent risk of illicit appropriation of this type of knowledge in order to block communities’ access to their own intellectual production (inherent to them). In that sense, the present academic work will focus on studying the way in which the protection of TK is proposed in Peru, analyzing its effectiveness and deficiencies. Likewise, new measures will be proposed for the purpose of complementing and improving the system.